User interface for mobile learning / Syed Rahazuan Syed Deraman - Syed Deraman, Syed Rahazuan (2002)
This paper issues the user interface design for the new implementation of learning - through mobile devices. Mobile learning is now growing rapidly in today world and the presentation of learning content through mobile devices makes the developer surrounds with limitations. First, this paper will view project that had been and still develop in this area to absorb the problem that they faced. This paper will discuss the potential issues that arise when designing the user interface for a small scale device with limit screen display. The usage of mark-up languages for wireless devices is also viewed. At the end of this paper will focus on the implementing the user interface due to the problem that viewed. Finally, the snapshot of UiTM Mobile Learning prototype for the future work is viewed.